2014
DOI: 10.1136/neurintsurg-2014-011229
|View full text |Cite
|
Sign up to set email alerts
|

The LVIS/LVIS Jr. stents in the treatment of wide-neck intracranial aneurysms: multicentre registry

Abstract: The LVIS/LVIS Jr. stent system is safe and effective for the treatment of wide-neck intracranial aneurysms, providing suitable support of the coil mass, which allows for a high level of occlusion with low rates of recanalisation and subsequent treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
87
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 21 publications
10
87
0
1
Order By: Relevance
“…14 This difference may have prevented incomplete stent opening in the 20 stents deployed in this series. This adverse event occurs at a rate of 6%-7% with the LVIS Jr. 24,25 One technical complication, stent migration into the aneurysm after deployment, developed in 1 of our patients, but this complication did not result in any clinical consequences. Stent migration during deployment was reported by using other types of open-cell or closed-cell stents, but migration may be more of a concern with low-profile braided stents because they have a lower radial force.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…14 This difference may have prevented incomplete stent opening in the 20 stents deployed in this series. This adverse event occurs at a rate of 6%-7% with the LVIS Jr. 24,25 One technical complication, stent migration into the aneurysm after deployment, developed in 1 of our patients, but this complication did not result in any clinical consequences. Stent migration during deployment was reported by using other types of open-cell or closed-cell stents, but migration may be more of a concern with low-profile braided stents because they have a lower radial force.…”
Section: Discussionmentioning
confidence: 70%
“…24,25 Finally, the LEO Baby stent fits inside microcatheters with luminal diameters of 0.0165 inches; therefore, these stents may exhibit improved navigation within arteries or through already-deployed stents. The struts of LEO Baby stents are not fixed (ie, the struts can move over each other); this feature makes room for the second stent and decreases the constraint on the second stent at the level of the stent intersection.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate complete occlusion rate was 73%. Poncyljusz et al 18 reported an immediate complete occlusion rate of 85% by using either LVIS or LVIS Jr stents. The immediate total occlusion rate of 75% in our study is comparable with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recently published multicenter registry on the use of the LVIS stent (MicroVention, Tustin, California) in treating wide-neck aneurysms found complete and near-complete occlusion rates of 82% and 6%, respectively. 13 Flow diverters such as the Pipeline Embolization Device (Covidien, Irvine, California) and Silk Device (Balt Extrusion, Montmorency, France) are increasingly being used in the treatment of complex, wide-neck intracranial aneurysms, particularly aneurysms of the ICA. In the Pipeline for Uncoilable or Failed Aneurysms clinical trial including over 100 patients with large and giant wide-neck ICA aneurysms, the rate of complete angiographic occlusion at 12 months was 87%, with only 5.5% of patients having residual aneurysm.…”
Section: Discussionmentioning
confidence: 99%